The Impact of Growth Performance and Political Regime Type on Economic Policy Liberalization - Hans Pitlik (Austrian Institute of Economic Research (WIFO), 2007)
The paper investigates empirically the interaction between economic growth performance and political institutions in producing free-market reform. In particular, we explore whether political regime types systematically shape government policy responses to good or bad growth performance, employing panel econometric techniques and using recently updated data for economic reform and political institutions. Contrary to conventional wisdom we find that a bad growth performance is conducive to reforms only in democracies, but not in autocracies. Democratic rule seems to be favourable for policy liberalisation in general, but a very good growth performance weakens liberalisation incentives considerably.
Keywords: 330; democracy; crisis hypothesis; market-oriented reform; political credibility; Wirtschaftswachstum; Wirtschaftsreform; Deregulierung; Politisches System; Schätzung; Welt